2013
DOI: 10.1149/2.031310jes
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Effect of Varying Vinylene Carbonate (VC) Content in Lithium Ion Cells on Cycling Performance and Cell Impedance

Abstract: LiCoO2/graphite and Li[Ni1/3Mn1/3Co1/3]O2/graphite pouch cells and Li[Ni1-x-yMnxCoy]O2/graphite 18650 cells were made with varying concentrations of vinylene carbonate (VC) and studied using high precision coulometry, extended cycling as well as electrochemical impedance spectroscopy (EIS). As expected, adding increased concentrations of VC (up to 6 wt%) to the control electrolyte resulted in improved coulombic efficiency, decreased charge endpoint slippage and longer cycle life. However, high concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
138
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(155 citation statements)
references
References 16 publications
5
138
2
Order By: Relevance
“…Significantly lower CE values indicate side reactions connected to irreversible capacity loss as shown by high precision measurements by Dahn's group. 21,[43][44][45] For the measurements at 25…”
Section: Resultsmentioning
confidence: 99%
“…Significantly lower CE values indicate side reactions connected to irreversible capacity loss as shown by high precision measurements by Dahn's group. 21,[43][44][45] For the measurements at 25…”
Section: Resultsmentioning
confidence: 99%
“…However, since it is known that LCO cathodes can also form a resistive surface film in the presence of VC additive (presumably consisting of poly(VC) 8,9 ), an assignment of the overall cell impedance growth to the individual contributions from anode and cathode requires more advanced techniques, like the symmetric cell approach. 10 Thus, later on, Burns et al 10 investigated the effect of VC (0 -6 wt%) over extended charge/discharge cycling of graphite/NMC 18650 cells on anode and cathode impedance growth via symmetric cell measurements. They showed that indeed the impedance of the negative electrode increases nearly linearly with VC concentration, whereas the impedance of the positive electrode first decreases as the VC concentration is increased to 2 wt% and then only increases gradually at higher VC concentrations.…”
mentioning
confidence: 99%
“…11 Vinylene carbonate (VC) has been commonly used as an additive for forming a robust negative electrode SEI and has been shown to improve the cycle life and calendar life of Li-ion cells. [12][13][14] Ethylene sulfite (ES) was reported to form a protective SEI film on the negative electrode. [15][16][17] Ternary additives of 2% propene sultone (PES), 1% ethylene sulfate (DTD) and 1% tris(-trimethylsilyl)-phosphite (TTSPi) (called PES211) improved the cycle and calendar life of NMC/graphite Li-ion cells under normal (i.e., 4.2 V) and high voltage (i.e., 4.4 V) operation.…”
mentioning
confidence: 99%
“…12,26 Symmetric cells were constructed from electrodes after dissembling some of these pouch cells. The detailed procedures for symmetric cell construction have been described by Petibon et al 26 The pouch cells were charged or discharged to 3.8 V and held at 3.8 V for one hour (approx.…”
mentioning
confidence: 99%